A Ratiometric Fluorescent Probe for Imaging of the Activity of Methionine Sulfoxide Reductase A in Cells. Issue 41 (14th September 2016) - Makukhin, Nikolai; Tretyachenko, Vyacheslav; Moskovitz, Jackob; Míšek, Jiří
Abstract: Methionine sulfoxide reductase A (MsrA) is an enzyme involved in redox balance and signaling, and its aberrant activity is implicated in a number of diseases (for example, Alzheimer's disease and cancer). Since there is no simple small molecule tool to monitor MsrA activity in real time in vivo, we aimed at developing one. We have designed a BODIPY‐based probe called ( S )‐Sulfox‐1, which is equipped with a reactive sulfoxide moiety. Upon reduction with a model MsrA ( E. coli ), it exhibits a bathochromic shift in the fluorescence maximum. This feature was utilized for the real‐time ratiometric fluorescent imaging of MsrA activity in E. coli cells. Significantly, our probe is capable of capturing natural variations of the enzyme activity in vivo. Abstract : Oxidative stress? Relax, we got a probe for that: Aberrant activity of methionine sulfoxide reductase A (MsrA) is implicated in a number of diseases. A fluorescent probe enabling real‐time imaging of the activity of MsrA is reported. The probe is bright, water‐soluble, photostable, and sensitive enough to capture natural variations of MsrA in cells.